Combining C reactive protein and serum albumin to predict 90-day mortality in systemic lupus erythematosus with serious community-acquired infections. Issue 1 (12th July 2021) - He, Shuangjun; Tang, Chao; Yu, Jie; Ma, Jun; Qiao, Minjie; Zhou, Wei; Chen, Yi; Zhang, Xingyu
Abstract : Objective: Serious infections in SLE are common and have emerged as the major cause of death. However, effective methods to identify poor prognosis are still lacking. Therefore, we aimed to determine the predictive value of C reactive protein (CRP) plus albumin (ALB) in SLE with serious infections. Methods: From May 2015 to December 2018, consecutive patients with SLE presenting with serious infections in our emergency department were prospectively recruited. Serum CRP and ALB were measured within 24 hours of admission. The outcome was defined as mortality rate at 90 days. A CRP plus ALB score (2–6) was assigned based on the CRP and ALB concentrations. We performed univariate and multivariate regression analyses to detect the independent effects of CRP plus ALB on 90-day mortality (all-cause and infection-related). Subgroup analyses were used to show the effects stratified by lupus nephritis. Results: A total of 150 patients were included, and the all-cause 90-day mortality rate was 38% (n=57), 41 of which was infection-related. The predominant infection sites were pulmonary (79.3%) and bloodstream infection (20.7%). Serum CRP and ALB levels were significantly different in non-surviving patients compared with those in surviving patients (p=0.002 and p<0.001, respectively). In the fully adjusted logistic regression model, the CRP plus ALB score was associated with decreased 90-day survival (adjusted OR 1.52; 95% CI 1.08 to 2.13; p=0.017). Conclusions: CRP plus ALB was associated with the risk of all-cause and infection-related 90-day mortality in SLE with serious infections. Although this finding requires further verification, the two parameters may be useful for predicting poor outcomes in such patients.